2019
DOI: 10.5194/essd-2018-164
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EDGAR v4.3.2 Global Atlas of the three major Greenhouse Gas Emissions for the period 1970–2012

Abstract: Abstract. The Emissions Database for Global Atmospheric Research (EDGAR) compiles anthropogenic emissions data for greenhouse gases (GHG) and for multiple air pollutants based on international statistics and emission factors. EDGAR data provides quantitative support for atmospheric modelling and for mitigation scenario and impact assessment analyses as well as for policy evaluation. The new version v4.3.2 of the EDGAR emission inventory provides global estimates, disaggregated to IPCC-relevant source-sector le… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 11 publications
1
91
0
1
Order By: Relevance
“…However, the EDGAR (emissions database for global atmospheric research) GHG emission data for the base year 2015 can be comparatively analyzed as shown in Figure 7. The EDGAR estimates of the GHG emissions for 2015 pertaining to CO 2 are 39,301.7 kton; for N 2 O, 0.31 kton; and for CH 4 , 1.05 kton [89]. Similarly, the results of this study estimated that in the base year 2015, CO 2 , N 2 O, and CH 4 emissions were 39,437.9 kton, 0.25 kton, and 1.39 kton, respectively, which are close to the referred database.…”
Section: Resultsmentioning
confidence: 99%
“…However, the EDGAR (emissions database for global atmospheric research) GHG emission data for the base year 2015 can be comparatively analyzed as shown in Figure 7. The EDGAR estimates of the GHG emissions for 2015 pertaining to CO 2 are 39,301.7 kton; for N 2 O, 0.31 kton; and for CH 4 , 1.05 kton [89]. Similarly, the results of this study estimated that in the base year 2015, CO 2 , N 2 O, and CH 4 emissions were 39,437.9 kton, 0.25 kton, and 1.39 kton, respectively, which are close to the referred database.…”
Section: Resultsmentioning
confidence: 99%
“…(d) Chinese national territorial‐based emissions based on different data sources. Data source: national and provincial data provided by National Bureau of Statistics (), Multiresolution Emission Inventory for China (MEIC, ), Emissions Database for Global Atmospheric Research (Janssens‐Maenhout et al, ), Carbon Dioxide Information Analysis Centre (Boden et al, ), Global Carbon Budget (Le Quéré et al, ), International Energy Agency (IEA, ), and British Petroleum (BP, ).…”
Section: Resultsmentioning
confidence: 99%
“…China is currently the largest emitters of anthropogenic N 2 O emissions globally (Zhou et al, 2014). Over the past decades, this source in China increased with N-fertilizer use, accounting for over 20% of global cropland-N 2 O emissions from IPCC Tier 1 inventories (FAO, 2018;Janssens-Maenhout et al, 2019;Winiwarter, Höglund-Isaksson, Klimont, Schöpp, & Amann, 2018).…”
Section: Introductionmentioning
confidence: 99%